2014
DOI: 10.1590/s0102-79722014000100004
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of the athletic identity measurement scale (AIMS-Plus) for the portuguese population

Abstract: Athletic Identity may be defi ned as being the degree of importance, strength and exclusivity that is attached to the athlete's role which is maintained by him/herself and his/her context (Cieslak, 2004). In this study, using a confi rmatory factor analysis, the measure of Athletic Identity (AIMS-plus) was examined. A total of 650 athletes completed the AIMS-plus. The psychometric features of the original scale were replicated to the Portuguese population. Validity and reliability were positive. AIMS-plus and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…The three-factor higher order structure is also in line with what emerged in recent cross-cultural validations [10,11,13] and consolidates the construct of Athletic Identity and the validity of the AIMS across different countries and cultures. It should be noted that in recent years, some authors have suggested an expansion of this instrument [12], with the addition of a further sub-dimension (i.e., "positive affectivity") and a split of "social identity" into "social" and "self-identity". However, these studies need to be extended and the three-factor model proposed by Brewer and Cornelius [6] remains the more consolidated to date.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The three-factor higher order structure is also in line with what emerged in recent cross-cultural validations [10,11,13] and consolidates the construct of Athletic Identity and the validity of the AIMS across different countries and cultures. It should be noted that in recent years, some authors have suggested an expansion of this instrument [12], with the addition of a further sub-dimension (i.e., "positive affectivity") and a split of "social identity" into "social" and "self-identity". However, these studies need to be extended and the three-factor model proposed by Brewer and Cornelius [6] remains the more consolidated to date.…”
Section: Discussionmentioning
confidence: 99%
“…To explore these aspects of the self, it would have been necessary to adopt other existing scales validated for an Italian speaking population, but there appears to be a lack of these measures with a sole religious identity measure [35] recently validated. On the other hand, it would have been possible to validate more general measures of self-concept for the Italian context, such as the Tennessee Self-concept scale (TSCS-2 [36]), but we considered a priority for the Italian sporting context the translation of the AIMS, which is a scale specific for the sport domain and has received widespread use across several countries [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the model's invariance in two independent samples was supported, indicating cross validity. This is a pivotal step when evaluating psychometric properties of a measurement scale (Marôco, 2010), and this procedure has been reported when validating scales in recent studies conducted in the sports scenario (e.g., Alvarado, Sandín, Valdez-Medina, González-Arratia, & Rivera, 2012;Biscaia, Correia, Ross, Rosado, & Mâroco, 2013;Cabrita, Rosado, Leite, & Sousa, 2013;Theodorakis, Dimmock, Wann, & Barlas, 2010). population to better understand engagement among athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the possible cultural differences in the process of self-identity, it is beneficial to explore the structure of athlete identity in non-English-speaking culture. These studies involved people of different languages and cultures such as Russian, 9 Portuguese, 10 Hong Kong, 11 Greek, 12 Brazilian, 13 Turkish, 14 Japanese, 15 and extended to special groups such as athletes with disabilities. 16 With the validation of AIMS in different cultures, some researchers have revealed the existence of other dimensions of AIMS.…”
Section: Psychologymentioning
confidence: 99%